Chemopreventive effect of artesunate in 1,2-dimethylhydrazine-induced rat colon carcinogenesis - Sazal Patyar; Rakesh Raman Patyar; Bikash Medhi; Krishan Lal Khanduja (Wolters Kluwer Medknow Publications, 2017)
Artesunate (ART) is a semisynthetic derivative of artemisinin. Artemisinin and its derivatives have shown profound cytotoxicity and antitumor activity in addition to antimalarial activity in various studies. As the in vivo chemopreventive efficacy of ART in colon carcinogenesis has not been investigated so far, the aim of the current study was to study the chemopreventive effect of ART in 1,2-dimethylhydrazine (DMH)-induced rat colon carcinogenesis. Animals were divided into four groups (n = 6): Group I - vehicle (1 mM ethylenediaminetetraacetic acid), Group II - DMH (20 mg/kg), Group III - DMH + 5-fluorouracil (81 mg/kg), Group IV - DMH + ART (6.7 mg/kg). After completion of 15 weeks of treatment, rats were sacrificed under ether anesthesia by cervical dislocation for assessment of lipid peroxidation (LPO), antioxidant status, average number of aberrant crypt foci (ACF), and cytokine levels. ART administration significantly decreased the average number of ACF/microscopic field. Similarly, LPO level was decreased and antioxidant activities were enhanced after ART treatment. ART decreased the levels of proinflammatory cytokines and induced apoptosis in the colons of DMH-treated rats. The results of this study suggest that ART has a beneficial effect against chemically induced colonic preneoplastic progression in rats.